Trends in Natality Data in the United States. Issue 3 (May 2020) - Simpson, Kathleen Rice
Abstract : There are a number of important resources to help nurses stay up-to-date on natality trends in the United States. Key data are presented with highlights on changes in the data from 2017 to 2018 collected from birth certificates. In 2018, compared to 2017, there were fewer births, teen births, cesareans, births of multiples, and more preterm births, labor inductions, and births attended by certified nurse midwives. The day and month with highest number of births remain Thursday and August, while Sunday and February are still the day and month with the lowest number of births.